2021
DOI: 10.3390/biology10040307
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs: Pleiotropic Impacts on Breast Cancer Metastasis and Their Clinical Perspectives

Abstract: As a major threat factor for female health, breast cancer (BC) has garnered a lot of attention for its malignancy and diverse molecules participating in its carcinogenesis process. Among these complex carcinogenesis processes, cell proliferation, epithelial-to-mesenchymal transition (EMT), mesenchymal-to-epithelial transition (MET), and angiogenesis are the major causes for the occurrence of metastasis and chemoresistance which account for cancer malignancy. MicroRNAs packaged and secreted in exosomes are term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 182 publications
0
6
0
Order By: Relevance
“…Currently, the potential of exomiRs is being assessed as a novel therapy strategy of cancer and other diseases [ 171 , 172 , 173 ]. In BC, c-miRNAs and exomiRs have been shown to affect essential features such as tumor growth, invasion and angiogenesis [ 174 ]. For example, the circulating exosomal miRNAs miR-92 and miR-25-3p in BC patients can induce angiogenesis and epithelial–mesenchymal transition (EMT).…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Currently, the potential of exomiRs is being assessed as a novel therapy strategy of cancer and other diseases [ 171 , 172 , 173 ]. In BC, c-miRNAs and exomiRs have been shown to affect essential features such as tumor growth, invasion and angiogenesis [ 174 ]. For example, the circulating exosomal miRNAs miR-92 and miR-25-3p in BC patients can induce angiogenesis and epithelial–mesenchymal transition (EMT).…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…There is a need to understand the molecular mechanism in chemoresistance to minimize the recurrence rate. Many studies showed the role of exosomal miRNA in the induction of chemoresistance in breast cancer ( Tang et al, 2021 ). Here, we review some signaling pathways that are specifically targeted by exosomal miRNA to regulate the particular drug sensitivity of breast cancer (see Table 1 ).…”
Section: Exosomal Micrornas In Bc For Chemoresistancementioning
confidence: 99%
“…Another class of potential biomarkers present in circulation are small noncoding microRNAs (miRNAs), which play roles in the regulation of gene expression [ 118 ]. miRNAs secreted from exosomes improved the migration capacity of several BC cell lines [ 119 , 120 ]. miR-105, miR-122, and miR-106b are characteristically expressed and secreted by metastatic BC cells, promoting invasion and metastasization [ 110 , 121 ].…”
Section: Hsp27 Hsp60 Hsp70 and Hsp90 In Bc Therapeutics: Negative Cha...mentioning
confidence: 99%